Peripheral Retinal Degenerations Optical Coherence Tomography and Retinal Laser Coagulation - Shaimova, Venera A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an illustrated guide to peripheral retinal degenerations and the role of spectral domain coherence tomography (SD-OCT) in diagnosis and treatment. The book discusses 73 clinical cases and gives detailed information on the principles of SD-OCT and its application in the imaging of peripheral retina. Peripheral Retinal Degenerations: Optical Coherence Tomography and Retinal Laser Coagulation, 2nd edition, discusses a broad range of retinal pathologies such as chorioretinal degenerations, posterior vitreous detachment, vitreoretinal adhesions and tractions and includes a plethora of high-quality clinical images throughout. Ophthalmologists and retinal specialists will find this updated edition to be the perfect didactic resource for furthering skills and knowledge in this clinical area. .
Principles and methods of peripheral retina OCT scanning -- Optical coherence tomography of the peripheral retina and the vitreoretinal interface -- Peripheral retinal degenerations as a risk factor for rhegmatogenous retinal detachment -- Intraretinal degenerations -- Vitreoretinal degenerations -- Chorioretinal degenerations -- Retinal laser photocoagulation in peripheral degenerations. .
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology